Museum Artifact Conservation Training for Social Science Educators and Students in Pontianak - Haris Firmansyah; Andang Firmansyah; Putri Tipa Anasi; Nur Meily Adlika; Yusawinur Barella; Venny Karolina; Aminuyati (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The West Kalimantan Museum stores and exhibits a collection of items with historical, scientific, artistic, and cultural significance, primarily originating from West Kalimantan Province. It is crucial for social science educators and students in West Kalimantan to comprehend the significance of visiting the museum in person. This allows them to directly witness and study historical and cultural artifacts of West Kalimantan, thereby reinforcing the knowledge they acquire from books. Hence, social science education lecturers of Tanjungpura University organized a community service program known as